Mental Health of Elderly in Singapore: The Influence of Living Arrangement, Loneliness, and Perceived Problems - Soh, Lin Ken (2017)
With an increasingly aging population and decreasing old age support ratio in Singapore, there is a need to better understand how possible shifts in living arrangement and other key factors might affect elderly mental health. The author previously found that perceived problems moderate the relationship between living arrangement and mental health. However, literature has recently shown that loneliness mediates the relationship between living arrangement and mental health. The current study combines both research, and aims to clarify the role of perceived problems in the living arrangement, loneliness, and mental health relationship. [1st Award]